Nucleophilic 5-endo-trig Cyclization of 3,3-Difluoroallylic Ketone Enolates: Synthesis of 5-Fluorinated 2-Alkylidene-2,3-dihydrofurans - Fujita, Takeshi; Sakoda, Kotaro; Ikeda, Masahiro; Hattori, Masahiro; Ichikawa, Junji (Synlett, 2013)
3,3-Difluoroallylic ketones readily undergo nucleophilic 5-endo-trig cyclization through their metal enolates to afford 5-fluorinated 2-alkylidene-2,3-dihydrofurans. O-Cyclization exclusively occurred via intramolecular substitution of the vinylic fluorines.
Keywords: cyclization; fluorine; alkenes; furans; 5-endo-trig; ketone enolates; vinylic substitution